Interaksi Sosial sebagai Mediator Kunci Dinamika Pembelajaran Pendidikan Jasmani - Pulung Riyanto; Heri Yusuf Muslihin; Andang Rohendi (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
This study aims to analyze the dynamics of the learning process and student learning outcomes by placing social interaction as a mediating variable in Physical Education, Health, and Recreation students at Musamus University. The study used a quantitative approach with an explanatory research design and data analysis based on Structural Equation Modeling (SEM) with Partial Least Squares (PLS). Data were collected through a Likert-scale questionnaire that measured the variables of the learning process, social interaction, and learning outcomes, and supported by student academic data. The results showed that the learning process has a significant relationship with social interaction and student learning outcomes. Social interaction was also proven to have a significant effect on learning outcomes and acts as a mediating variable that strengthens the relationship between the learning process and learning outcomes. These findings confirm that the quality of social interaction is a key factor in increasing student engagement and multidimensional learning outcomes. This study provides theoretical contributions in the development of social interaction-based learning models as well as practical implications for lecturers in designing more collaborative, participatory, and contextual learning to improve the quality of student learning outcomes in higher education.